A redox-responsive mesoporous silica nanoparticle capped with amphiphilic peptides by self-assembly for cancer targeting drug delivery1. Issue 22 (14th June 2015) - Xiao, Dong; Jia, Hui-Zhen; Ma, Ning; Zhuo, Ren-Xi; Zhang, Xian-Zheng
<x xml:space="preserve">Abstract</x> A novel redox-responsive mesoporous silica nanoparticle (RRMSN/DOX) capped with amphiphilic peptides by self-assembly was demonstrated for targeting drug delivery in cancer cells.